Recent studies on polymeric materials for supercapacitor development - Loganathan, N.N. (Elsevier Ltd, 2022)
Supercapacitors are heavily researched in the field of energy storage due to their benefits, including high power density and cyclic stability compared to batteries. Although supercapacitors have limitations such as low energy density, development on polymers have made advancements on those limitations. This review seeks to describe the vast role that polymers play in the development of supercapacitors over the past decade. It explains the construction and classifies the components of a supercapacitor. Further, it touches on conducting polymers and the difference between synthetic polymers and biopolymers. An in-depth analysis of commonly studied polymeric materials are presented with systematic reporting and critical analysis of existing work. A summary of the findings together with foreseen challenges and future prospects are presented at the end of the review. Previous reviews have identified and explained the role that conducting polymers play in the synthesis of active supercapacitor electrodes. Rather, this review investigates the role of all polymeric materials in the development of both active and passive supercapacitor components. Â© 2022 Elsevier Ltd